Where I Live - Spinelli, Eileen; Phelan, Matt (New York : Dial Books for Young Readers, 2007)
In a series of poems, Diana writes about her life, both before and after her father loses his job and she and her family move far away to live with Grandpa Joe.
Keywords: Moving -- Fiction; Family life -- Fiction; Astronomy -- Fiction